Pengaruh CR, DER, dan ROA Terhadap Return Saham Sektor Basic Materials di BEI Periode 2020-2024 - Hellen Andriyani; Trisnadi Wijaya (MDP Student Conference, 2026)
This study aims to determine the effect of CR, DER, and ROA on the Stock Returns of the Basic Materials sector on the Indonesia Stock Exchange (IDX) for the period 2020-2024, both partially and simultaneously. This research uses a quantitative approach with an associative method. The data used are secondary data in the form of annual financial statements of companies obtained from the Indonesia Stock Exchange (IDX). The sampling technique was carried out using purposive sampling. The population in this study consists of 113 companies, while the sample in this study amounts to 63 companies with a total of 315 observations. Hypothesis testing in this study uses Multiple Linear Regression, accompanied by Classical Assumption Tests, Partial Tests (t-test), Simultaneous Tests (f-test), and the coefficient of determination (R²). The results of the Partial Test (t-test) indicate that the ROA variable has a significant effect on Stock Returns, while the CR and DER variables do not have a significant effect on Stock Returns. Based on the results of the simultaneous test (f-test) CR, DER, and ROA have a significant effect on Stock Returns in the Basic Materials sector.